1967
DOI: 10.1063/1.1709160
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Crystalline Orientation of Sputtered Ferromagnetic Films on Amorphous Substrates

Abstract: The effects of thermionic sputtering parameters on crystalline orientation and coercive force of magnetic films are discussed in this paper. By controlling the crystalline orientation within the film it is possible to produce films with a coercive-force range from 0.9 Oe to 35.8 Oe. The crystalline orientation is controlled by the magnetic field, the electric field, and the substrate position within the apparatus. All of the films were prepared on substrates which were not exposed to the sputtered material unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1969
1969
1987
1987

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Even a very small field, as small as 10Vcm -~ , affects the coalescence stage of metallic films [4]. Significant changes in the structure and growth behaviour of the oriented films have been reported [5][6][7] on application of a transverse field.Recently we have reported [8][9][10] the influence of the application of a longitudinal electric field at the time of deposition of CdS films and found that electrical quenching is responsible for various observations. The present studies on the X-ray structural characterization of CdS films is an extension of similar results.…”
mentioning
confidence: 99%
“…Even a very small field, as small as 10Vcm -~ , affects the coalescence stage of metallic films [4]. Significant changes in the structure and growth behaviour of the oriented films have been reported [5][6][7] on application of a transverse field.Recently we have reported [8][9][10] the influence of the application of a longitudinal electric field at the time of deposition of CdS films and found that electrical quenching is responsible for various observations. The present studies on the X-ray structural characterization of CdS films is an extension of similar results.…”
mentioning
confidence: 99%